Multi-faceted ethnic identity of Indigenous groups in East Malaysia: profound economic and political implications from a legal perspective / Bromeley Philip and Simon Engka Crown - Philip, Bromeley; Crown, Simon Engka (Universiti Teknologi MARA, Sabah, 2023)
The paper discusses some definitions of indigenous people, looking into some elements that characterise the concept of "indigenous". It needs to be mentioned that the focus of this paper is specifically from a legal perspective. The concept and definitions of "indigenous or native" are understood in the light of the legal framework. Hence, it looks into statutory definitions as found in the Federal Constitution as well as in the local constitutions and legislations of Sabah and Sarawak. The aim of the paper is to discuss how a native status is established in the context of the existing local legislation and judicial argumentation, particularly native land ownership and political implications involving native status identification based on local legislation and judicial interpretations. Ethnic identity in the two states is rather ambiguous and complex in East Malaysia in particular. The meanings and implications of ethnic identities in legal aspects might change subject to social, economic, and political situations. The concept of ethnic identity does not have to do purely with being born of ethnic origin. In fact, in some cases, ethnic identity can be situational in nature as "...it could be learned, cultivated and embraced over a period of time.